Design of the novel ThermoBrachy applicators enabling simultaneous interstitial hyperthermia and high dose rate brachytherapy. (1st January 2021) - Androulakis, Ioannis; Mestrom, Rob M. C.; Christianen, Miranda E. M. C.; Kolkman-Deurloo, Inger-Karine K.; van Rhoon, Gerard C.
Abstract: Objective: In High Dose Rate Brachytherapy for prostate cancer there is a need for a new way of increasing cancer cell kill in combination with a stable dose to the organs at risk. In this study, we propose a novel ThermoBrachy applicator that offers the unique ability to apply interstitial hyperthermia while simultaneously serving as an afterloading catheter for high dose rate brachytherapy for prostate cancer. This approach achieves a higher thermal enhancement ratio than in sequential application of radiation and hyperthermia and has the potential to decrease the overall treatment time. Methods: The new applicator uses the principle of capacitively coupled electrodes. We performed a proof of concept experiment to demostrate the feasibility of the proposed applicator. Moreover, we used electromagnetic and thermal simulations to evaluate the power needs and temperature homogeneity in different tissues. Furthermore we investigated whether dynamic phase and amplitude adaptation can be used to improve longitudinal temperature control. Results: Simulations demonstrate that the electrodes achieve good temperature homogeneity in a homogenous phantom when following current applicator spacing guidelines. Furthermore, we demonstrate that dynamic phase and amplitude adaptation provides a great advancement for further adaptability of the heating pattern. Conclusions: This newly designed ThermoBrachy applicator has the potential to revise the interest in interstitial thermobrachytherapy, since the simultaneous application of radiation and hyperthermia enables maximum thermal enhancement and provides maximum efficiency for patient and organization.